FUSTER-BEWAT SCORE VERSUS IDEAL CARDIOVASCULAR HEALTH SCORE TO PREDICT LEFT VENTRICULAR HYPERTROPHY: DATA FROM CHINA PEACE MILLIONS PERSONS PROJECT. (April 2021) - Liu, Lin; Huang, Yuqing; Huang, Jiayi; Chen, Chaolei; Yu, Yuling; Shen, Geng; Feng, Yingqing
Abstract: Objective: The Fuster-BEWAT Score (FBS) has been recently developed for use in lifestyle-based cardiovascular disease prevention, presenting similar accuracy in predicting subclinical atherosclerosis with ideal cardiovascular health score (ICHS), but it is unclear whether these scores exhibit comparable predictive values for detection of left ventricular hypertrophy (LVH). We evaluated the effectiveness of ICHS and FBS in assessing the presence of LVH among Chinese population. Design and method: A total of 3, 521 participants aged 35 to 75 years with echocardiography screening in Guangdong were enrolled in the China PEACE (Patient centered Evaluative Assessment of Cardiac Events) Millions Persons Project. Subjects were grouped into three categories according to the number of favorable ICHS or FBS: ideal, intermediate, and poor. Left ventricular mass index (LVMI) was assessed by left ventricular mass divided by body surface area. LVH was defined as LVMI > = 115 g/m 2 in male and LVMI > = 95 g/m 2 in female. Results: In this study, poor ICHS accounts for 14.3% of all participants, intermediate ICHS 78.2%, and ideal ICHS 7.6%; poor FBS accounts for 4.4% of all participants, intermediate FBS 65.4%, and ideal FBS 30.2%. With poor ICHS as references, those with intermediate and ideal ICHS showed substantially lower adjusted odds of having LVH (odds ratio (OR) [95% confidence interval (CI)]: 0.643 [0.417, 0.991] and 0.346 [0.219, 0.547], respectively, with a p-value for trend < 0.001). Compared with participants with poor FBS, intermediate and ideal FBS were negatively associated with the likelihood of LVH (OR [95%CI]: 0.638 [0.512, 0.796] and 0.316 [0.211, 0.473], respectively, with a p-value for trend < 0.001). The Receiver Operating Characteristic Curve (ROC) indicated identical discriminating accuracy of ICHS (Area Under Curve (AUC): 0.696) and FBS (AUC: 0.702) with DeLong's test p-value 0.172 in identifying LVH. Figure. No caption available. Conclusions: Both ICHS and FBS predict the presence and extent of subclinical atherosclerosis with similar accuracy, highlighting the value of the FBS as a simpler and more affordable score for evaluating the risk of LVH.